TRIBUN SEPAKBOLA BERBASIS ALAM SEBAGAI TEMPAT BERAKTIVITAS PUBLIK DI KELURAHAN KALIANYAR - Christopher Tjandrawira; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2020)
As one of the most populous sub-districts in Jakarta ,Kalianyar is experiencing social and health problems due to lack of green space which causes lack of space for activities and the emergence of various diseases. Kalianyar actually has a soccer field that can be used as a substitute for a green space, but until now, it has never been used because of its hidden location and exclusivity. This project aims to utilize the field to become a third place with natural nuances that can accommodate the activities of the community. A field, which is merely space, will not immediately become a